Effect of Temperature and Cellulose Mol Ratio on the Optimization of Oxalic Acid Production from Kapok Fiber - Akren Alvindo Pratama; Shofwatul Athiyah; Retno Dewati (G-Tech: Jurnal Teknologi Terapan, 2025)
Until now, kapok fiber has not been fully utilized. However, kapok fiber has a high cellulose content that can be used as a basic material in the manufacture of oxalic acid. The purpose of this study was to determine how the hydrolysis temperature and the number of moles of cellulose affect the oxalic acid content produced from kapok fiber. This research was conducted in four stages, namely hydrolysis, precipitation, acidification, and crystallization. Oxalic acid crystals were then analyzed using permanganometric titration to determine the levels contained, melting point analysis, and pH to compare the characteristics of the synthesized oxalic acid with standard oxalic acid. In addition, FTIR spectroscopy analysis to determine the functional groups contained in oxalic acid. The results showed that the highest oxalic acid content was obtained in the condition of 1 mole cellulose and 70°C hydrolysis temperature, which amounted to 17.45%. The FTIR analysis results of synthetic oxalic acid and standard oxalic acid show similarities, as seen from the O-H group length of 3406.29 cm⁻¹, the C=O group length of 1687.71 cm⁻¹, the C-O group length of 1132.21 cm⁻¹, and the C-H group length of 669.30 cm⁻¹.